Transdermal iontophoretic drug delivery: advances and challenges. (27th May 2016) - Ita, Kevin
Abstract: The stratum corneum continues to pose considerable impediment to transdermal drug delivery. One of the effective ways of circumventing this challenge is through the use of iontophoresis. Iontophoresis uses low-level current to drive charged compounds across the skin. This review discusses progress made in the field of iontophoretic transport of small and large molecules. The major obstacles are also touched upon and advances made in the last few decades described. A number of iontophoretic systems approved for clinical use by regulatory authorities is also discussed.